Zoo-technical characteristics of Koshur goat An unexplored goat genetic resource of Kashmir - Rathar, Mubashir A.; Alam, Safeer; Shanaz, S; Khan, Nusrat N; Majid, Rukhsana; Ahmad, Tavseif; Hamdani, Ambrin (Indian Farming, 2021)
There is great scope for rearing of goat for meat and milk production under backyard goat keeping, semi intensive and intensive rearing management system. However, there is no effective goat development programme operational at the moment. A complete study in respect to breeding, nutrition, management, health care and economics is required to organize for improvement of these goats. Characterization and documentation of this non-descript goat’s population is highly recommended.